Typically developed adults and adults with autism spectrum disorder classification using centre of pressure measurements - Goh, Kwang Leng; Morris, Susan; Rosalie, Simon; Foster, C.; Falkmer, Torbjorn; Tan, Tele (2016)
Autism spectrum disorders (ASD) are neurodevelopmental disorders which affect a persons ability to interact with the world around him/her. Emerging studies have shown abnormal postural control in people with ASD. The aim of this study was to enable the classification of adults with ASD and typically developed (TD) adults based on force plate measurements of centre of pressure. Nineteen typical adults and eleven adults diagnosed with ASD primarily high functioning autism or Asperger's syndrome participated in this study. A correlation-based feature selection algorithm was used to evaluate the quality of the attributes and the results have achieved up to 0.976 classification accuracy.